Edible films and coatings for shelf life extension of mango: a review. Issue 9 (30th March 2022) - Tavassoli-Kafrani, Elham; Gamage, Mala Villaddara; Dumée, Ludovic F.; Kong, Lingxue; Zhao, Shuaifei
Abstract: Edible films and coatings are eco-friendly promising materials for preserving the quality and extending the shelf life of fresh and minimally-processed fruits. They can form protective layers around fruits, regulate their respiration rates, and protect them from loss of water, tissue softening, browning, and microbial contamination. Edible films and coatings have many advantages over other post-harvest treatments. They can add commercial value to fruits by enhancing their appearance, and act as carriers of functional ingredients, such as antioxidants, antimicrobial agents and nutraceuticals. Mango, a highly perishable tropical fruit, has a short post-harvest life, which limits transport to distant markets. Application of edible films and coatings on mango fruits is an effective method to preserve their quality and safety. This paper provides an overview of desirable properties for films and coatings, and recent development in different edible coatings for both fresh and minimally-processed mango. The most popular edible coating materials, such as chitosan, waxes, starch, gums, and cellulose used for mango are reviewed. The commercialization of coating formulations and equipment used for application of coatings are discussed. The environmental impacts, safety aspects, and the challenges encountered are outlined. The opportunities to use other coating materials, such as aloe-vera gel, microbial polysaccharides, and photosynthetic microorganisms are also examined.